Ileocolic intussusception due to a cecal endometriosis: Case report and review of literature - Emmanuel Rivkine; Léa Marciano; Claude Polliand; Antonio Valenti; Marianne Ziol; Christophe Poncelet; Christophe Barrat (BMC, 2012)
Abstract Cecal endometriosis and ileocolic intussusception due to a cecal endometriosis is extremely rare. We report a case of a woman who presented an ileocecal intussusception due to a cecal endometriosis. The patient gave two months history of chronic periombilical pain requiring regular hospital admission and analgesia. The symptoms were not related to menses. A laparotomy was performed and revealed an ileocolic intussusception. The abdominal exploration did not find any endometriosis lesion. Ileocaecal resection was performed. Microscopic examination showed a cystic component, lined by a regular cylindric epithelium. Foci of endometrial tissu were oberved in the cecal subserosa and muscularis mucosal, with irregular endometrial glands lined by cylindric epithelium without atypia immunostained with CK7, and characteristic endometrial stroma immunostained with CD10. Cecal endometriosis and ileocolic intussusception due to a cecal endometriosis is extremely rare. Diagnose of etiology remains challenging due to the absence of clinical and radiological specific characteristics. Virtual slide The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/2975867306869166